Amazon region: eco-efficient landscapes - Fonte, Steven J.; González, A.; Graefe, Sophie; Guimarães, E.; Perpétuo MG; Jarvis, Andy; Lavelle, Patrick M.; Lundy, Mark M.; Peters, Michael; Quintero, M.; Rao, Idupulapati M.; Tapasco, Jeimar; et al. (2013)
The Amazon Basin is so diverse that one could say many Amazons exist, not just one. Indeed, its diversity is considered unique in the world. Although the Basin occupies 7% of the planet’s land, it carries 25% of the world’s terrestrial biodiversity. The region is so vast, it represents one-third of South America’s land surface. It covers, or partly covers, nine countries: Colombia (36% of the land area), Venezuela and Guyana (6% each), Suriname and French Guiana (almost 100% each), Brazil (60%), Bolivia and Peru (75% together), and Ecuador (45%).